Microalgae as Biosensors for Heavy Metal Detection Using Spectroscopic Techniques - Sara Hammoud Abdulameer (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Heavy metal pollution in aquatic ecosystems represents a persistent environmental challenge due to their non-biodegradable nature and bioaccumulation in the food chain, posing severe risks to human and ecological health. Specific Background: Traditional detection techniques like atomic absorption and ICP-MS are effective but expensive and time-consuming, driving interest toward biological alternatives such as microalgae-based biosensors that can detect and respond to pollutants through physiological and biochemical changes. Knowledge Gap: Limited studies have compared the biosensing capacities of Ankistrodesmus falcatus and Scenedesmus obliquus using integrative spectroscopic and metabolomic analyses under realistic contamination conditions. Aims: This study investigates the biosensing and bioremediation abilities of these two microalgal species in detecting lead, cadmium, and mercury in contaminated water. Results: Both species showed high metal removal efficiency (up to 97% for Hg²⁺), with Ankistrodesmus exhibiting faster biosorption and stronger sensitivity, while Scenedesmus demonstrated higher resilience to lead. Spectroscopic analyses revealed distinct functional group shifts, reduced chlorophyll fluorescence, and metabolic reprogramming under metal stress. Novelty: The integration of FTIR, fluorescence, and GC-MS analyses provided a comprehensive biochemical understanding of algal stress responses. Implications: These findings support the development of cost-effective, eco-friendly biosensing systems for monitoring and remediating heavy metal pollution in aquatic environments.Highlight : Two algal species showed strong potential as biosensors for detecting heavy metal contamination in water. Spectroscopic analyses confirmed biochemical and physiological changes under metal exposure. Ankistrodesmus responded faster to mercury, while Scenedesmus showed better tolerance to lead. Keywords : Microalgae, Heavy Metal Pollution, Biosensing, Spectroscopic Techniques, Water Quality